Soluble monomeric human programmed cell death-ligand 1 inhibits the functions of activated T cells - Liang, Zhaoduan; Chen, Wenfang; Guo, Yunzhuo; Ren, Yuefei; Tian, Ye; Cai, Wenxuan; Bao, Yifeng; Liu, Qi; Ding, Peng; Li, Yi (Frontiers in Immunology, 2023)
The presence of soluble human programmed cell death-ligand 1 (shPD-L1) in the blood of patients with cancer has been reported to be negatively correlated with disease prognosis. However, little information exists about the mechanisms underlying high levels of shPD-L1 for promoting disease progression. In this study, we found that the apoptosis of human peripheral PD-1+CD4+ T cells was significantly elevated in patients with cancer compared with healthy donors and was positively correlated with circulating PD-L1 levels in patients with cancer. In vitro, monomeric shPD-L1 significantly inhibited the proliferation, cytokine secretion, and cancer cell-killing activity of peripheral blood mononuclear cells (PBMCs) activated by either agonist antibodies or HATac (high-affinity T cell activation core)-NYE (NY-ESO-1 antigen). It also promoted CD4+ T cells to express forkhead family transcription factor 3 (FoxP3) for the conversion of induced T regulatory cells, which was more significant than that mediated by soluble human PD-L1 fusion protein (shPD-L1-Fc). These results confirm that soluble PD-L1 could be a candidate for inducing peripheral exhausted T cells, promoting peripheral tolerance to tumor cells, and implicating in system tumor immune escape in addition to the tumor microenvironment. This is an important mechanism explaining the negative correlation between peripheral blood PD-L1 levels and cancer prognosis. Therefore, understanding the roles of hPD-L1 in peripheral blood will be helpful for the development of precision immunotherapy programs in treating various tumors.